Surveillance in Countries with Limited Resources - Damani, Nizam (International Journal of Infection Control, 2008)
Basics surveillance is an essential component of all infection control programme with aim to identify outbreaks and to establish baseline rate of infections in a healthcare facilities. The surveillance data can be used to identify preventable infections so that resources are targeted in high priority areas requiring minimum resources. Different methods of surveillance exist and the type of surveillance method depends on the local factors, i.e. the type and size of hospital, case mix and availability of resources. Targeted surveillance aimed at high risk areas, procedure directed or specific type of infections associated with high morbidity or mortality are more cost effective and are manageable in various healthcare settings worldwide.